Comparative study to assess the effect of chewing stick and toothbrush on oral hygiene, gingival health and pocket depth among patients attending dental outpatient clinic in Udaipur, India - A. Agrawal; N. Bhatt; K. K. Shivlingesh; K. Singh; H. Chaudhary; S. Sen roy (Nigerian Dental Association, 2010)
Objective: The purposes of this study was to assess and compare the oral hygiene, gingival health and pocket depth among patients using miswak (Salvadora Persica L) and toothbrush. Method: A total of 528 subjects participated in this study (63.6% females and 36.4% males), ranging in age from 20 to 45 years (mean = 35.43 ± 12.83). After fulfilling the entry criteria participants were classified according to their oral hygiene habits as miswak users (group I), tooth brush and paste users (group II) or both miswak users and tooth brush and paste users (group III). All subjects were assessed using Simplified Oral Hygiene Index (OHI-S), gingival index, pocket depth and gingival recession. Result: There was no statistically significant difference of mean OHI-S scores between miswak (1.04±0.64), toothbrush (1.08± 0.71) and combined users (1.09±0.74). On the other hand, all the three groups differ significantly in relation to mean gingival index scores, miswak (0.95±0.63), toothbrush (1.20± 0.59) and combined users (1.44±0.71) (p= 0.000). Also, Group II (3.90±1.88) demonstrated a significantly higher mean pocket depth than Group I (3.31±2.12) (p=0.019). However, gingival recession was significantly higher in Group I (2.17±1.64) in comparison to Group II (1.37±1.35) and Group III (1.30±1.58) (P=0.000). Conclusion: This study demonstrated that, miswak (Salvadora Persica L) users exhibited good oral hygiene and gingival index score but they had higher gingival recession scores which may influence the periodontal health.